EVALUASI PROGRAM BADAN RESTORASI GAMBUT DALAM MERESTORASI HUTAN DAN LAHAN GAMBUT DI KEPENGHULUAN TELUK NILAP KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR TAHUN 2018 - Rulia Ananti; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Presidential Regulation Number 1 of 2016 concerning the Peat Restoration Agency in Article 1 explains that the Peat Restoration Agency is a non-structural institution that is under and responsible to the President. The Peat Restoration Agency was established on January 6, 2016 with the aim of accelerating the recovery and restoration of the hydrological function of damaged peat especially due to fire and drying. The Peatland Restoration Agency has a 3R program, namely rewetting (wetting), revegetation and revitalization of the community economy.            The purpose of this study is to describe the evaluation of the Peatland Restoration Agency program in restoring forests and peatlands in Kepenghuluan Teluk Nilap then also to find out the factors that influence the evaluation of the Peat Restoration Agency in restoring forests and peatlands in Kepenghuluan Teluk Nilap, Kubu Babussalam District, Rokan Hilir Regency in 2018. The theoretical concept used is the CIPP model program evaluation theory (Context, Input, Process and Product) by Daniel Stufflebeam. This type of research is descriptive qualitative. The data collection technique is done by interview and documentation.            The result of this research is that the evaluation of the Peatland Restoration Agency program, especially in the rewetting program (wetting) with canal blocking construction activities in Kepenghuluan Teluk Nilap have not been running optimally. The canal blocking construction has not been able to completely wet the peat so that hotspots are still found in the Kepenghuluan Teluk Nilap. The factors that influence the evaluation of the Peatland Restoration Agency program in canal blocking development activities are the lack of resources used, delays in budget distribution, inconsistencies in peat restoration plans, lack of regulations for peat restoration activities, the lack of a role for the Government of Kepenghuluan and the public mindset that many have not. understand about the peat restoration program. Keywords: Restoration, Rewetting, Canal Blocking, Evaluation